PRACTICE-ORIENTED LEARNING OF BACHELORS OF ADVERTISING AND PUBLIC RELATIONS - Horbenko, Н. (Continuing Professional Education: Theory and Practice, 2023)
The tendency of practice-oriented learning as a modern method of improving of the Ukrainian education and the problem of elaboration of mechanism of interaction between institution of higher education and potential employer, realization of which is possible due to implementation of practice-oriented learning, are considered in the article. The principles of practice-oriented learning, which require active methods of forming of student competences based on interaction, but not only passive learning of material, development of competences, which correspond to modern business practice, are researched. In particular, meaning of the notion practice-oriented learning is defined, its necessity of introduction in the training of bachelors of advertising and public relations is explained, its scientific and methodological disadvantages are emphasized, essence and importance of applied bachelor’s programme, which includes active participation in education of partner companies, are presented, peculiarities of practice-oriented learning technologies are revealed. Also experience of realization of practice-oriented learning in Borys Grinchenko Kyiv University is described. Achievements of students of the Chair of Advertising and Public Relations, which were based on principles of practice-oriented education, are reviewed.